The Use of Milk and Flour Made from Almonds in the Productionof Lactic Foods - Chatinyan, N. R.; Karakhanyan, M. G.; Dallakyan, N. S. (ՀԱԱՀ հիմնադրամ)
A nation’s health and mental strength depend on its food consumption which is one of the main conditions for the full functioning of the human body. In modern times, the demand for sour milk products has increased significantly due to their dietary and medicinal features. The research object was pure cow’s milk, almond milk, almond flour, and samples of sour milk products. During the work, a study of the physicochemical and sensory indicators of the raw materials added almond milk, and the finished product was performed. Based on the sensory and physicochemical indicators of the product, the optimal dosages are as 70 % of cow’s milk, 30 % of almond milk, and 1.5 % of almond flour were determined. Based on the above, it is recommended to introduce the developed technology of lactic acid products in production, which will complement the assortment of sour milk products, enrich the chemical composition of the product, and increase the body’s resistance and digestibility.
Keywords: Food Science and Technology